Convergence of finite difference schemes for nonlinear complex reaction-diffusion processes - Araújo, Adérito (2015)
This paper is devoted to the proof of the convergence properties of a class of finite difference schemes applied to nonlinear complex reaction-diffusion equations. We investigate the accuracy of the numerical solution considering implicit and semi-implicit discretizations. To illustrate the theoretical results we present some numerical examples computed with a semi-implicit scheme applied to a nonlinear equation.